2013
DOI: 10.1111/joa.12079
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis of osteonal architecture in bones from healthy young human male subjects using scanning electron microscopy

Abstract: The shape and structure of bones is a topic that has been studied for a long time by morphologists and biologists with the goal of explaining the laws governing their development, aging and pathology. The osteonal architecture of tibial and femoral mid-diaphyses was examined morphometrically with scanning electron microscopy in four healthy young male subjects. In transverse sections of the mid-diaphysis, the total area of the anterior, posterior, lateral and medial cortex sectors was measured and analysed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 31 publications
1
16
2
Order By: Relevance
“…However, compared with the 4–5% frequency of sealed + partially sealed osteons reported by Congiu & Pazzaglia () and the 2.2% reported in their subsequent study (Pazzaglia et al. ), we found that far fewer (~ 0.1%) osteons in our three groups of non‐human bones were sealed or partially sealed.…”
Section: Discussioncontrasting
confidence: 59%
See 4 more Smart Citations
“…However, compared with the 4–5% frequency of sealed + partially sealed osteons reported by Congiu & Pazzaglia () and the 2.2% reported in their subsequent study (Pazzaglia et al. ), we found that far fewer (~ 0.1%) osteons in our three groups of non‐human bones were sealed or partially sealed.…”
Section: Discussioncontrasting
confidence: 59%
“…Congiu & Pazzaglia (2011) reported that the percentage of sealed and partially sealed osteons from amputated tibiae from three patients (ages 25, 28, and 52 years) was 4.2 and 1.7%, respectively. However, in a later study of tibial and femoral mid-diaphyses from four healthy young males (ages 25, 28, 30, and 32) who underwent amputations because of traumatic limb injuries, they found that only 2.2% of the total osteons were sealed (Pazzaglia et al 2013 The relatively small sample of human femora in patients without hip replacements likely accounts for the seemingly paradoxical finding that OPD in that group is considerably higher than in the F, ÀHR group even though the mean age of this latter group is 27 years older (i.e. older bones should have higher OPD) (Britz et al 2009).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations